Revitalizing basic life support certification: insights into blended learning / Mohd Fazrul Mokhtar and Suraya Abdul-Razak - Mokhtar, Mohd Fazrul; Abdul-Razak, Suraya (Universiti Teknologi MARA, 2024)
The primary objective of the Basic Life Support (BLS) course is to impart high-quality cardiopulmonary resuscitation skills, regardless of participants' background. Traditionally, this course has been a one-day program involving classroom instruction, live demonstrations, and assessments. However, the COVID-19 pandemic exposed limitations in conventional BLS training and certification, prompting the adoption of innovative teaching methods. To address current challenges and ensure timely skill enhancement for healthcare professionals, we introduced a blended learning approach to the BLS course. This paper presents the development process of a hybrid BLS learning management system, encompassing curriculum design, validation, website development, and usability testing. During content validation, 10 experts were involved, and amendments were made based on feedback given which resulted in a final item-content validity index (I-CVI) = 1 for all training videos. In its inaugural year, the hybrid BLS course conducted 28 sessions and successfully trained 493 participants, primarily healthcare professionals. Notably, 92.3% of participants provided a System Usability Scale (SUS) score >68%, indicating a positive user experience. Participants also emphasized the user-friendly interface with easy navigation and content effectiveness. This outcome highlights the practicality of delivering BLS using a blended learning approach, which not only improves course administration but also has the potential of income revenues through professional certification programme.